(untitled) (Bangladesh Journal of Microbiology, 2008)
This study reports on the microbiological status of dried milk samples belonging to eleven different companies. With few exceptions, the microbial counts of the milk samples were within the acceptable limits as specified by international authorities. Aerobic plate counts ranged from 1.4 x 101 - 4.4 x 104 cfu/g and the number of Staphylococcus varied from 6.0 x 101 - 8.2 x 102 cfu/g. Presence of Staphylococcus in most of the samples indicates post-processing contamination of the milk. Coliform organisms and Salmonella were not detected from any of the samples tested. Yeasts or molds were found in the samples of four manufacturers but their counts were very low. Since the international agencies have not fixed any limit for Staphylococcus count in dry milk, the results of the present study indicate that powder milk products were of good quality from microbiological point of view. Keywords: Dried milk, Microbial enumeration, Codex, ICMSF DOI: http://dx.doi.org/10.3329/bjm.v23i2.885 Bangladesh J Microbiol, Volume 23, Number 2, December 2006, pp 162-164